Exploring the Relationship Between Profitability, Leverage, and Sales Growth with Firm Value: The Moderating Role of Company Size in Indonesia's Food and Beverage Sector - Mokhamad Afrizal Arnaz; Lucky Nugroho (Baca Dulu Publisher, 2024)
This investigation aims to evaluate the impact of profitability, leverage, and sales growth on company value, with company size serving as a moderating variable. The consumer goods industry sector of the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2018-2022 period is the primary focus of this research. The issues raised include the impact of profitability, leverage, and sales growth on the company's value, as well as the extent to which the company's size moderates the influence of these variables on the company's value. The quantitative approach is employed in the research method, panel data regression. Purposive sampling was employed to select 95 companies for the research sample. The study's findings indicate that the company's value is substantially and positively influenced by profitability and sales growth, while leverage has no significant impact. It has been demonstrated that the impact of profitability, leverage, and sales growth on company value is moderated by the company's scale. The implications of this study are related to the necessity for companies in the food and beverage sector to concentrate on enhancing profitability and managing leverage to optimize company value. This investigation is novel in that it investigates the role of firm scale as a moderation variable in the relationship between financial factors and firm value, particularly in a dynamic economic context.